A European Academy of Neurology guideline on medical management issues in dementia. (26th July 2020) - Frederiksen, K. S.; Cooper, C.; Frisoni, G. B.; Frölich, L.; Georges, J.; Kramberger, M. G.; Nilsson, C.; Passmore, P.; Mantoan Ritter, L.; Religa, D.; Schmidt, R.; Stefanova, E.; et al.
Abstract : Background and purpose: Dementia is one of the most common disorders and is associated with increased morbidity, mortality and decreased quality of life. The present guideline addresses important medical management issues including systematic medical follow‐up, vascular risk factors in dementia, pain in dementia, use of antipsychotics in dementia and epilepsy in dementia. Methods: A systematic review of the literature was carried out. Based on the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) framework, we developed a guideline. Where recommendations based on GRADE were not possible, a good practice statement was formulated. Results: Systematic management of vascular risk factors should be performed in patients with mild to moderate dementia as prevention of cerebrovascular pathology may impact on the progression of dementia (Good Practice statement). Individuals with dementia (without previous stroke) and atrial fibrillation should be treated with anticoagulants (weak recommendation). Discontinuation of opioids should be considered in certain individuals with dementia (e.g. for whom there are no signs or symptoms of pain or no clear indication, or suspicion of side effects; Good Practice statement). Behavioral symptoms in persons with dementia should not be treated with mild analgesics (weak recommendation). In all patients with dementia treated with opioids, assessment of the individual risk–benefit ratio should be performed at regular intervals. Regular, preplanned medical follow‐up should be offered to all patients with dementia. The setting will depend on the organization of local health services and should, as a minimum, include general practitioners with easy access to dementia specialists (Good Practice statement). Individuals with dementia and agitation and/or aggression should be treated with atypical antipsychotics only after all non‐pharmacological measures have been proven to be without benefit or in the case of severe self‐harm or harm to others (weak recommendation). Antipsychotics should be discontinued after cessation of behavioral disturbances and in patients in whom there are side effects (Good Practice statement). For treatment of epilepsy in individuals with dementia, newer anticonvulsants should be considered as first‐line therapy (Good Practice statement). Conclusion: This GRADE‐based guideline offers recommendations on several important medical issues in patients with dementia, and thus adds important guidance for clinicians. For some issues, very little or no evidence was identified, highlighting the importance of further studies within these areas.